Short-term prognosis of childhood hepatoblastoma in relation to ERCC1 C118T single nucleotide polymorphism and VEGF expression - Wen, Yuan; Zhang, Weiling; Zhang, Yi; Hu, Huimin; Li, Jing; Huang, Dongsheng (Polish journal of pathology, 2019)
To evaluate the short-term prognosis of pediatric hepatoblastoma (HB) in relation to excision repair cross-complementation gene 1 (ERCC1) C118T single nucleotide polymorphism (SNP) and VEGF expression. ERCC1 C118T SNP and VEGF expression were detected and investigated in 31 children with HB undergoing platinum-based chemotherapy, to analyze their relationship with short-term pediatric HB prognosis. CC (38.7%; 12/31), CT (35.5%; 11/31), and TT (25.8%; 8/31) ERCC1 C118T mutation types were identified. The Kaplan-Meier survival curve analysis showed that the CC group had a better short-term prognosis than the CT + TT group (p = 0.010). VEGF was overexpressed in 14 cases (45.2%) and underexpressed in 17 cases (54.8%). The Kaplan-Meier survival curve analysis showed that the high VEGF expression group showed poorer short-term prognosis than the lower VEGF expression group (p = 0.004). In this study, ERCC1 C118T SNP in children with HB was mainly found to be mutant type CT + TT. Compared to wild type CC, children with the mutant type CT + TT exhibited better treatment efficacy and remission with platinum-based chemotherapy as well as better survival rates. Moreover, the short-term prognosis of children with low VEGF expression was better than in those with high expression.